Time for policy redemption: a review of the evidence on the disclosure of criminal records - Weaver, Beth (The Scottish Centre for Crime & Justice, 2018)
There is wide variation in disclosure practices within and between the U.S, the U.K and Europe, although there is some consensus that reasons for checking criminal records by employers include: minimising risk of liability and loss; concerns surrounding public protection where the nature of employment includes working with vulnerable groups; assessments of moral character in terms of honesty and trustworthiness; and compliance with statutory occupational requirements (Blumstein and Nakamura, 2009). As the use of criminal record background checks by employers has become increasingly pervasive, having a criminal record can have significant effects on employment prospects producing ‘invisible punishment’ or ‘collateral consequences’ of contact with the justice system (Travis 2002). Taking into account that over 38% of men and 9% of women in Scotland are estimated to have at least one criminal conviction (McGuinness, McNeill and Armstrong, 2013), issues surrounding criminal record checking and disclosure in an employment context affect a large proportion of people.